(untitled) - Soukup, Tom (New York, 2002)
This book describes how various types of business problems can be solved using visual mining techniques. After introducing the business issues and fundamentals, it then presents a step-by-step methodology for implementing visual mining techniques into your own business intelligence project.
Keywords: Data mining,Database searching,Information visualization,Khai thác dữ liệu,Tìm kiếm cơ sở dữ liệu,Thông tin ảo